Teks Ucapan Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim Naib Canselor Universiti Malaysia Pahang Sempena Welcoming Speech for Academic Rally On Engineering Technology (1) - Pejabat, Naib Canselor UMP (Universiti Malaysia Pahang, 2016)
First and foremost, I am truly delighted that I have the honour of welcoming our partner from Northern Illinois University who has been working with us closely since 2011 and also to the panels of the forum.